1988
DOI: 10.1210/jcem-67-3-541
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Neutralizing Antibodies During Intranasal Synthetic Salmon Calcitonin Treatment of Paget's Disease*

Abstract: Nine patients with Paget's disease were treated with 200 U (15 nmol) synthetic salmon calcitonin (sCT) intranasally (in)/day for 12 months. Five of them had received im or in sCT therapy for 1-4 yr up to 0.5-5 yr before this study. Low titer antibodies to sCT were detected in the serum of three of these five patients, but not in the four patients who had not received prior sCT therapy. After 2 months of in sCT administration, four of the former group, but none of the latter group, had antibodies to sCT. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Although without doubt the helical nature in the 12-22 region is established via sequential and medium range NOEs, the differentiation between an ␣-helix and a 3 10 -helix is, however, more difficult. Actually, the fact that ␣CH i -NH iϩ2 connectivities, not observable in an ␣-helix, are generally detected along the chain and in particular, in the Leu 12 -Tyr 22 region, suggests that we have a 3 10 ), not observable in a 3 10 -helix, also demonstrates that this part of the peptide could take up an ␣-helix. The simultaneous presence of NOEs peculiar to ␣-and 3 10 -helices can be interpreted as evidence of flexibility (31).…”
Section: Figmentioning
confidence: 83%
See 1 more Smart Citation
“…Although without doubt the helical nature in the 12-22 region is established via sequential and medium range NOEs, the differentiation between an ␣-helix and a 3 10 -helix is, however, more difficult. Actually, the fact that ␣CH i -NH iϩ2 connectivities, not observable in an ␣-helix, are generally detected along the chain and in particular, in the Leu 12 -Tyr 22 region, suggests that we have a 3 10 ), not observable in a 3 10 -helix, also demonstrates that this part of the peptide could take up an ␣-helix. The simultaneous presence of NOEs peculiar to ␣-and 3 10 -helices can be interpreted as evidence of flexibility (31).…”
Section: Figmentioning
confidence: 83%
“…Calcitonin (CT) can be used to treat various diseases including Paget's disease and osteoporosis (9), but the tendency of hCT to associate into amyloid fibrils at physiological pH limits its efficacy as a drug. Salmon CT (sCT) (Scheme 1), the clinically used alternative to hCT, causes immunogenic reactions (10). Therefore, understanding the mechanism of amyloid formation by hCT and controlling this process are important not only in the context of amyloid formation but also as a step toward improved therapeutic use of CT.…”
mentioning
confidence: 99%
“…However, the use of sCT has been shown to cause side effects, such as anorexia and vomiting (17,18), as well as to trigger immune reactions that could severely limit its effectiveness as a drug (19)(20)(21)(22)(23). Interestingly, it has been reported that hCT shows a much higher potency than the salmon variant under specific conditions where aggregation is prevented (24).…”
mentioning
confidence: 99%
“…Proteins administered via a s.c. or an intradermal route may be more immunogenic than when administered via other routes, probably by mimicking an active immunization process (64,65). Although theoretically local administration may be considered least likely to be associated with immunogenicity, Ab production can still occur such as with intranasal synthetic salmon calcitonin for Paget's disease or aerosolized recombinant human DNA for cystic fibrosis (66,67). The oral route offers an attractive alternative way to deliver protein therapeutics (68).…”
Section: Prediction Of Immunogenicitymentioning
confidence: 99%